Inventory and Disease Incidence in 38 Accessions of Taro Plants (Colocasia esculenta L.) in Jatinangor, Sumedang Regency, West Java - Yulia, Endah; Yunira, Alma; Hidayat, Syarif; Djaya, Luciana; Widiantini, Fitri; Suganda, Tarkus; Karuniawan, Agung (CROPSAVER, 2024)
Taro is an important agricultural commodity with considerable prospects for international market competition. However, its cultivation faces several challenges, particularly pathogen infections that can lead to substantial yield losses. Conducting a disease inventory in taro plants is essential for effective disease management and serves as a preliminary step in developing resistant taro varieties. This study aimed to document diseases affecting 38 accessions of taro plants. The research was conducted from August to October 2021 at the Ciparanje Jatinangor Experimental Field and the Phytopathology Laboratory within the Department of Plant Pests and Diseases at the Faculty of Agriculture, Universitas Padjadjaran, located in Sumedang Regency. The methodology employed both qualitative and quantitative descriptive approaches. Data collection involved observing the incidence and severity of diseases, as well as identifying the pathogens responsible for the diseases. A total of 292 taro plants were examined during this study. The diseases identified included brown leaf spot (Cladosporium colocasiae), shot hole (Phoma sp.), orange leaf spot (Neojohnstonia colocasiae), white leaf spot (putative Pseudocercospora colocasiae), and leaf blight (Phytophthora colocasiae), along with other symptoms suspected to be caused by root pathogens and viruses.The most prevalent disease observed at the experimental site was brown spot disease, while leaf blight was identified as the most damaging. The incidence of leaf spot and leaf blight reached 100% across nearly all accessions of taro planted at the research site, with the highest severity of disease recorded at 49.65%.